The Use of Differentiated Digital Learning Models to Enhance Science Problem-Solving in Elementary Schools - Framz Hardiansyah; Tri Sukitman; Agus Wahdian; Hodairiyah Hodairiyah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Differentiated learning is a way to identify talents and teach according to students' different learning styles. Digital-based differentiated learning is an innovation in elementary school teaching and learning processes. This research aims to determine the use of digital-based differentiated learning models in improving science problem-solving in elementary schools because students tend to experience difficulties understanding the material taught in science subjects, and students are still lacking in developing the ability to solve science questions. This research method used quantitative research methods with the Pre-Experimental Design One Group Pretest-Posttest research model. The research sample consisted of 29 grade IV students who had a learning style of 76% visual, 14% auditory, and 10% kinesthetic. Data collection techniques used tests and questionnaires. Data analysis techniques used the Z test and the Mann-Whitney U test. The research results for the Mann-Whitney test obtained a significance value of 0.001, meaning 0.001 0.05, so Ho was rejected, and Ha was accepted. Thus, the use of digital-based differentiated learning models can improve science problem-solving in elementary schools. The research findings indicate that digital-based differentiated learning models significantly enhance science problem-solving abilities.